Evaluation of Coastal Resilience in Residential Buildings - Graciano-Martinez, Andrea Yohana; Olortigue-Cabanillas, Jomira Joana; Cruzado-Palacios, María Delia; Zamora-Terrones, Leydy Nataly (LACCEI, 2025)
The objective of this research is to evaluate the level of coastal resilience in residential buildings of the AAHH La Florida Baja, Chimbote 2024. The research method is quantitative and descriptive. The design is non-experimental. The technique used is observation in the AAHH La Florida Baja. The data collection instrument is the observation sheet structured in the three specific objectives; determine the vulnerability, identify the adaptive design and characterize the green infrastructure of the residential buildings of the AAHH La Florida Baja, in this, the observation sheet is composed of dynamic marking boxes qualified by an ordinal scale from 1 to 4, where the level of resilience of the residential buildings located in the coastal strip of the AAHH La Florida Baja - Chimbote is determined. The study determined that "The coastal communities of Florida Baja Chimbote face an uncertain future due to the lack of resilience of residential buildings to extreme weather events." Therefore, the level of coastal resilience of residential buildings in the AAHH. Low Florida is low.